ANALISIS FAKTOR-FAKTOR YANG MENENTUKAN RATING OBLIGASI SYARIAH PADA PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Elviza; Lilis Maryasih (Asosiasi Dosen dan Praktisi Ekonomi Nusantara, 2024)
The research aims to analyze the factors that determine the rating of sharia bonds in companies listed on the Indonesia Stock Exchange. The factors tested in this research are profitability ratios, liquidity ratios, solvency ratios and bond life as independent variables while the sharia bond rating is the dependent variable. The research sample consisted of 29 company bonds that were listed on the Indonesia Stock Exchange (BEI) and submitted financial reports to Bapepam in the 2015-2017 period. The data used in this research is secondary data and the sample selection used the purposive sampling method. The analytical tools used are discriminant analysis and logistic regression analysis. The results of hypothesis testing show that all variables can be used to determine bond ratings for companies that issue sharia bonds and are listed on the Indonesia Stock Exchange (BEI). Hypothesis testing using logistic regression analysis shows that 29 companies that issued sharia bonds from 2015 to 2017 had a high liquidity value, so the company received a bond rating with an AAA investment grade rating.